Changes of Metabolites in Acute Ischemic Stroke and Its Subtypes - Wang, Xin; Zhang, Luyang; Sun, Wenxian; Pei, Lu-lu; Tian, Mengke; Liang, Jing; Liu, Xinjing; Zhang, Rui; Fang, Hui; Wu, Jun; Sun, Shilei; Xu, Yuming; et al. (Frontiers in Neuroscience, 2021)
The existing techniques have many limitations on the diagnosis and classification of ischemic stroke (IS). We used metabolomics to screen the potential biomarkers of IS and its subtypes and to further explore the related pathophysiological mechanisms. Serum samples from 99 patients with acute ischemic stroke (AIS) (The AIS subtypes included 49 patients with large artery atherosclerosis and 50 patients with small artery occlusion) and 50 matched healthy controls (HCs) were analyzed by non-targeted metabolomics based on Liquid chromatography–mass spectrometry (LC-MS). Carry on the multivariate statistical analysis to the data to identify the potential biomarkers. There were 18 significantly differential metabolites such as Oleic acid, Linoleic acid, Arachidonic acid, L-Glutamine, L-Arginine and L-Proline between the patients with AIS and the HCs. These differential metabolites are closely related to many metabolic pathways, such as fatty acid metabolism and amino acid metabolism. There were also differences in metabolic profiling between the large artery atherosclerosis (LAA) group and the small artery occlusion (SAO) group. There were 8 differential metabolites such as L-Pipecolic acid, 1-Methylhistidine, PE, LysoPE, LysoPC, which affected Glycerophospholipid metabolism, Glycosylphosphatidylinositol(GPI)-anchor biosynthesis, Histidine metabolism, Lysine degradation. Our study identified the metabolic profiling of IS and its subtypes. The differential metabolites between the LAA and SAO may be potential biomarkers in clinical diagnosis. These results highlight the potential of metabolomics to reveal new pathways for IS subtypes and provides a new clue to explore the pathophysiological mechanism of IS and its subtypes.